Fertility of rat epididymal sperm after chemically and surgically induced sympathectomy - Kempinas, W. D.; Suarez, J. D.; Roberts, N. L.; Strader, L. F.; Ferrell, J.; Goldman, J. M.; Narotsky, M. G.; Perreault, S. D.; Evenson, D. P.; Ricker, D. D.; Klinefelter, G. R. (Soc Study Reproduction, 1998)
Guanethidine, a chemical that selectively blocks sympathetic noradrenergic neurons, was used to investigate the role of sympathetic innervation in the fertility of rat epididymal sperm, using both natural mating and in utero insemination protocols. This animal model correlates, at least in part, with spinal cord injury (SCI) in men. Adult male rats were treated daily by i.p. injections, for 21 or 42 days, with 0 or 6.25 mg/kg guanethidine. To compare the effects of guanethidine-induced sympathectomy with those following surgically induced sympathectomy, the inferior mesenteric ganglion and the proximal hypogastric nerves were removed in another group of rats. Both chemically and surgically induced sympathectomy increased the weight of the epididymis and seminal vesicles/coagulating glands as well as the number and the transit time of cauda epididymal sperm. Neither serum testosterone levels nor LH was affected by treatment with guanethidine. Using natural mating, no litters were produced by guanethidine-treated rats. Chemically denervated rats failed to produce copulatory plugs or ejaculate into the uterus. However, distal cauda epididymal sperm from chemically or surgically denervated rats displayed normal fertilization ability (80%) using in utero inseminations. In addition, the sperm of denervated rats did not show abnormal sperm chromatin structure using an assay that detects DNA damage. We conclude that sympathectomy delays the transit of sperm through the cauda epididymidis and produces ejaculatory dysfunction but does not compromise sperm quality in the distal cauda epididymidis. Moreover, these data provide compelling evidence that there is no association between the prolonged transit time of sperm within the epididymis, i.e., pre-ejaculatory sperm aging, and the fertility of those sperm, which has important implications for artificial insemination using sperm from men with SCI.